Composite Flap - Serratus Anterior with Rib Component – a Foot Salvage Solution after a Severe Crush Injury - Andrei MARIN; Carmen GIUGLEA; Silviu MARINESCU; Ruxandra MIHAI (Modern Medicine)
Severe work accidents are one of the most frequent causes for physical disability in adults, alongside car accidents and war/gunshot injuries. In this article we present the case of a severe crush injury of the left foot that occurred in a 31 year-old patient who was involved in a work accident. After an unsuccessful tissue coverage using local flaps, the salvage solution was that of a composite free flap, aiming not only to cover, but also to restore stability to the foot. The treatment of choice was the serratus anterior muscle harvested together with osseous component (8th rib). The healing was difficult, due to wound dehiscence with bone exposure over a small area, but the problem was addressed using FGF (fibroblast growth factor) sponges, which enabled granulation and complete wound closure. The outcome of the case was favourable, gait being possible without any deficiency. For the cosmetic and functional reasons, the patient suffered one last surgical procedure to debulk the dorsal aspect of the foot. The final result was more than satisfactory, the patient being totally rehabilitated and socially and professionally reintegrated.